Edaphic fertilization in the yield of Creole potato Solanum phureja (CIENCIA Y TECNOLOGÍA AGROPECUARIA, 2023)
The aim of this review article was to gather information on soil fertilization and its impact on the yield of Solanum phureja (creole potato). It addressed the existing issues in creole potato cultivation, characterized by the application of fertilizers without considering specific soil analyses of each plot or the critical extraction levels of the species, leading to high production costs, environmental contamination, and soil degradation. The methodology employed involved descriptive and analytical documentary research, analyzing articles collected over the last 20 years on soil fertilization in creole potatoes. The results underscored the importance of careful fertilization for creole potato cultivation, emphasizing that its success relies on ensuring the adequate availability of all necessary nutrients for the plant in the soil. It was concluded that future research should comprehensively address the fertilization of creole potato crops, particularly considering key elements such as nitrogen, phosphorus, and potassium
Keywords: Soils; nutrient availability; productivity